2018
DOI: 10.1038/s41594-018-0106-9
|View full text |Cite
|
Sign up to set email alerts
|

Terminal uridylyltransferases target RNA viruses as part of the innate immune system

Abstract: RNA viruses are a major threat to animals and plants. RNA interference (RNAi) and the interferon response provide innate antiviral defense against RNA viruses. Here, we performed a large-scale screen using Caenorhabditis elegans and its natural pathogen the Orsay virus (OrV), and we identified cde-1 as important for antiviral defense. CDE-1 is a homolog of the mammalian TUT4 and TUT7 terminal uridylyltransferases (collectively called TUT4(7)); its catalytic activity is required for its antiviral function. CDE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 48 publications
1
100
0
Order By: Relevance
“…Recent data hint at the importance of protecting the 3′ ends of viral RNAs as well, besides the 5′ ends, as it was shown that Tut4 and Tut7, 2 cellular terminal uridylyltransferases, can add one or 2 uridines to the 3′ ends of polyadenylated influenza mRNAs, as well as RNAs of several other viruses, to target these RNAs for degradation by cellular machineries [75][76][77]. Additionally, a recent report indicated that cytosolic coronaviral mRNAs are targeted by the cellular nonsense-mediated decay pathway, a pathway that detects aberrant translation termination DOI: 10.1159/000503030 features such as premature termination codons in mRNA, resulting in the degradation of these mRNAs [78].…”
Section: Viral Endoribonuclease Activitymentioning
confidence: 99%
“…Recent data hint at the importance of protecting the 3′ ends of viral RNAs as well, besides the 5′ ends, as it was shown that Tut4 and Tut7, 2 cellular terminal uridylyltransferases, can add one or 2 uridines to the 3′ ends of polyadenylated influenza mRNAs, as well as RNAs of several other viruses, to target these RNAs for degradation by cellular machineries [75][76][77]. Additionally, a recent report indicated that cytosolic coronaviral mRNAs are targeted by the cellular nonsense-mediated decay pathway, a pathway that detects aberrant translation termination DOI: 10.1159/000503030 features such as premature termination codons in mRNA, resulting in the degradation of these mRNAs [78].…”
Section: Viral Endoribonuclease Activitymentioning
confidence: 99%
“…DROSHA introduces a 39 staggered cut, liberating a small hairpin of~65 nt with a 2-nt 3 ′ overhang 40 (called pre-miRNA). Following pre-miRNA export to the cytoplasm, 41 DICER recognizes the 2-nt 3 ′ overhang on pre-miRNA using its platform 42 and PAZ domains ( Pre-miRNA with a relatively unstable 5 ′ end (e.g., mismatch, G-U, or 47 A-U pair) would be readily captured by the 5 ′ pocket (in the platform 48 domain) of DICER and the cleavage site is dictated by the distance from 49 3/51 the 5 ′ end ("5 ′ -counting rule") (Park et al, 2011;Tian et al, 2014). On 50 the other hand, pre-miRNA with a stable 5 ′ end (e.g., G-C pair) relies on 51 the interaction between its 3 ′ end and the 3 ′ pocket (in the PAZ domain) 52 of DICER and is cleaved at the site~22 nt away from its 3 ′ end 53 at both ends, which is subsequently loaded onto an Argonaute (AGO) 56 protein with the help from HSC70/HSP90 chaperone machinery (Iwasaki 57 et al, 2010; Naruse et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Terminal modification is critical in biology. For example, uridylation is implicated in tumorigenesis, proliferation, stem cell maintenance, and immune defense against viruses and retrotransposons (Blahna, Jones et al, 2011, Hagan, Piskounova et al, 2009, Jones, Quinton et al, 2009, Le Pen, Jiang et al, 2018, Warkocki, Krawczyk et al, 2018, Yeo & Kim, 2018). The C. elegans genome encodes three polyuridylation polymerases (PUPs): cde-1/pup-1/cid-1 , pup-2 and pup-3 (Kwak & Wickens, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These PUPs may have distinct roles in different cellular contexts. cde-1 is involved in the inheritance of RNAi, chromosome segregation and antiviral defense (Le Pen et al, 2018, van Wolfswinkel, Claycomb et al, 2009, Xu, Feng et al, 2018). CDE-1 functions with the RNA-dependent RNA polymerase (RdRP) EGO-1 and the Argonaute CSR-1 in the germline to affect chromosome segregation (Claycomb, Batista et al, 2009).…”
Section: Introductionmentioning
confidence: 99%